2020
DOI: 10.1002/aenm.201903240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorination on Lithium Transport and Short‐Range Order in Disordered‐Rocksalt‐Type Lithium‐Ion Battery Cathodes

Abstract: Fluorine substitution is a critical enabler for improving the cycle life and energy density of disordered rocksalt (DRX) Li‐ion battery cathode materials which offer prospects for high energy density cathodes, without the reliance on limited mineral resources. Due to the strong Li–F interaction, fluorine also is expected to modify the short‐range cation order in these materials which is critical for Li‐ion transport. In this work, density functional theory and Monte Carlo simulations are combined to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
183
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(191 citation statements)
references
References 45 publications
8
183
0
Order By: Relevance
“…Note that the greater discharge capacity at less fluorination (less Mn) suggests oxygen redox is more prone to participate in less fluorinated samples, meanwhile, the fluorination seems to affect the Li + extraction due to the possibility in modifying the cation short-range ordering. [11] Upon cycling, the capacity decay in less fluorinated samples is consistent with the loss of the highvoltage charge plateau and polarization buildup (Figure 2c and Figure S3, Supporting Information), which is also revealed in the dQ/dV profiles ( Figure S4, Supporting Information). The hysteresis and kinetics are examined by galvanostatic intermittent titration technique (GITT).…”
Section: Electrochemical Characterizationsupporting
confidence: 68%
“…Note that the greater discharge capacity at less fluorination (less Mn) suggests oxygen redox is more prone to participate in less fluorinated samples, meanwhile, the fluorination seems to affect the Li + extraction due to the possibility in modifying the cation short-range ordering. [11] Upon cycling, the capacity decay in less fluorinated samples is consistent with the loss of the highvoltage charge plateau and polarization buildup (Figure 2c and Figure S3, Supporting Information), which is also revealed in the dQ/dV profiles ( Figure S4, Supporting Information). The hysteresis and kinetics are examined by galvanostatic intermittent titration technique (GITT).…”
Section: Electrochemical Characterizationsupporting
confidence: 68%
“…[ 1–3 ] In recent years, lithium‐rich cation‐disordered rocksalt oxide cathodes have received significant attention because of their Co‐free chemistry, high energy density (>1000 W h kg −1 ) and high operating voltages, [ 4,5 ] making them attractive alternatives to the conventional layered cathode materials such as lithium nickel manganese cobalt oxides (LiNi x Mn y Co 1‐ x ‐ y O 2 , NMCs). [ 6,7 ] The large charge storage capacity in the DRX materials is attributed to the collective redox activities from a single‐ or multi‐electron pairs of TM cations, such as Ni 2+ /Ni 3+ , [ 8 ] Ni 2+ /Ni 4+ , [ 9–11 ] Mn 2+ /Mn 4+ , [ 12–14 ] Mn 3+ /Mn 4+ , [ 9,13,15–17 ] V 3+ /V 4+ , [ 18,19 ] V 4+ /V 5+ , [ 14 ] Cr 3+ /Cr 6+ , [ 19 ] Mo 3+ /Mo 5+ , [ 20 ] and Mo 3+ /Mo 6+ , [ 21 ] and oxygen anions (O 2− /O n − , 0 ≤ n < 2). [ 22–25 ] On the other hand, the d 0 TM elements ( e.g , 4 d Ti 4+ and Cr 6+ as well as 5 d Nb 5+ and Mo 6+ ) are essential for structural stability but they remain electrochemically inactive.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] In developing mitigation approaches to the drawback of irreversible oxygen redox behavior, computational modeling and experimental studies on partial substitution of oxygen by fluorine were attempted. [ 8–21,28 ] Table S1, Supporting Information, lists the fluorinated‐DRX compounds reported in the literature so far. In general, the F‐DRX cathodes were found to have better performance compared to their oxide counterparts, with less oxygen release, less impedance rise and better cycling stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lun et al 18 argued that the degree of fluorination has a significant impact on cathode material design, by improving the Li percolating network and thus achieving faster ionic diffusion. In addition, Ouyang et al 19 recently showed that fluorination can substantially affect SRO and, at sufficiently high concentrations, is beneficial to Li-ion transport.…”
Section: Introductionmentioning
confidence: 99%